2021
DOI: 10.25077/ar.8.2.131-147.2021
|View full text |Cite
|
Sign up to set email alerts
|

Laymen’s Narratives in Amouddou’s Eco-documentary: An Ecolinguistic Analysis

Abstract: Documentary films, generally of short or medium-length, have informative and educational purposes. They present authentic reports on areas of life, human activities, and the natural world. Particularly, eco-documentaries aim to raise environmental awareness towards the degradation of natural elements; they present alternatives for environmental issues such as pollution, global warming, and deforestation. To reinforce the argumentative process of environmental documentaries, laymen discourse contributes a lot t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study analyzing documentary films due to the environmental issues exposed the laymen's narrative parts which stated that the documentary films, in their laymen's narrative parts, frequently express fear and threat due to environmental issues such as pollution, global warming, or deforestation. The study also defined that the expression of fear and threat is commonly found in parts of the analysis (Mliless et al, 2021). Furthermore, a study analyzing the framing of animals in quranic discourse found that animals in Qur'an are framed into beings, benefactors, ornaments, and celestial signs.…”
Section: Ecolinguistics and The Previous Related Researchmentioning
confidence: 98%
“…A study analyzing documentary films due to the environmental issues exposed the laymen's narrative parts which stated that the documentary films, in their laymen's narrative parts, frequently express fear and threat due to environmental issues such as pollution, global warming, or deforestation. The study also defined that the expression of fear and threat is commonly found in parts of the analysis (Mliless et al, 2021). Furthermore, a study analyzing the framing of animals in quranic discourse found that animals in Qur'an are framed into beings, benefactors, ornaments, and celestial signs.…”
Section: Ecolinguistics and The Previous Related Researchmentioning
confidence: 98%
“…Further multimodal discourse analysis has been performed by Fernández-Vázquez (2021) to measure the environmental website communications of Latin American universities. Some other recent approaches include ecolinguistic analysis of news reports about the Sino-US trade war (Cheng and He, 2021), ecolinguistic discourse analysis of institutional documents to explore the ideological conflict (Niceforo, 2021), the ecolinguistic analysis of contemporary literary journalism literature (Alves, 2021), and ecolinguistic analysis of environmental documentaries considering the contribution of laymen discourses (Mliless et al 2021). Concerning an association between ecolinguistics and Covid-19, the analysis of ecological values of COVID-19 discourses (Misiaszek, 2021;Morozova & Pankevych, 2021) has recently been conducted.…”
Section: Research Questionsmentioning
confidence: 99%